2008
DOI: 10.1177/1043454207311742
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Survey of Nurses' Perceptions of Phase I Clinical Trials in Pediatric Oncology

Abstract: This study suggests that nurses' perceptions of pediatric oncology phase I clinical trials are diverse and mixed but are more likely to be positive than negative. Improving future treatments, medical benefit, improved quality of life, and hope were cited as potential benefits of phase I clinical trials, but nurses felt that families were hoping for a cure. Toxicities, false hope, and decreased quality of life were perceived as potential negative outcomes. Acting as a patient advocate was viewed as the most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…In such situations, the informants in the present study seemed to adhere to a care-centred ethic, i.e., the role as a nurse seemed to take priority over the task as a research assistant, and they described how they strived to act as the patient's advocate. The fact that nurses involved in clinical studies apprehend acting as a patient advocate as an important nursing task has previously been pointed out by Chang [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In such situations, the informants in the present study seemed to adhere to a care-centred ethic, i.e., the role as a nurse seemed to take priority over the task as a research assistant, and they described how they strived to act as the patient's advocate. The fact that nurses involved in clinical studies apprehend acting as a patient advocate as an important nursing task has previously been pointed out by Chang [7].…”
Section: Discussionmentioning
confidence: 98%
“…Some of these articles focus upon obtaining informed consent and working participant-centred [7,8,13]. Wilkes and Beale [42] found that one ethically troubling situation for research nurses can be the experienced role conflict between being a nurse providing care and being a research assistant.…”
Section: Introductionmentioning
confidence: 99%
“…The responsibilities of nurses caring for pediatric oncology patients are diverse, including serving as medical caregiver, advocate, educator, and research assistant 7 . Given the diverse functions of nurses caring for pediatric oncology patients, including the extended periods of intense face-to-face interactions, the impact that nurses have on patient and family decision-making processes is important to consider.…”
mentioning
confidence: 99%
“…A risk-benefit assessment must also take into consideration that studies of investigational drugs may be the last remaining treatment option for children with advanced cancer (Chang, 2008). Despite the less than 8% chance of positive response (Shah et al, 1998), patients and families may favorably view the potential for any amount of benefit.…”
Section: Beneficence: Definition and Applicationmentioning
confidence: 99%